Power Management in Multiuser Adaptive Modulation Transmission under QoS Requirements. (15th September 2013) - Althunibat, Saud; Zorba, Nizar; Skianis, Charalabos; Verikoukis, Christos
Abstract : A transmitter power management mechanism is presented in this paper where Multiple-Input Multiple-Output (MIMO) Multiuser Random Beamforming with Adaptive Modulation strategy is performed by the system. The objective of the proposed mechanism is quality of service (QoS) satisfaction for the scheduled user. The QoS is represented by the application demanded data rate and symbol error rate. The power outage problem is considered and a practical method to minimize the outage probability is proposed. The obtained results are encouraging as they show a great decrease in the system power budget. The multiuser system capability is also exploited to achieve larger power saving values and smaller probability of power outage by scheduling the user with the best channel characteristics at each time instant. The amount of saved power and the power outage probability are both presented through closed-form expressions. These theoretical results are compared to computer simulations, which show very good agreement in performance.